La reafirmación de las aportaciones de (propiedad de) los socios de las sociedades cooperativas. Propuesta de regulación de las sociedades de responsabilidad limitada cooperativa - García-gutiérrez Fernández, Carlos (REVESCO. Revista de Estudios Cooperativos, 2006)
The denominated International Norms (that are only European) of Accounting they have shown a latent problem that is not only terminological: they claim the resource consideration unaware of the heading that picks up the contributions of the partners of the cooperative societies, as it could not be otherwise when being companies in those that partner's condition is not acquired by the obligatory contribution (and, in its case, voluntary). The accounting seeks, among other things, to offer a faithful image of the patrimonial and economic-financial situation of the company. The principle of open door, settled down by the only worldwide organization! that what is a cooperative society, settles down it bears the refund of those contributions when the partner stops to be it; what configures to the inappropriately denominated social capital (it should be capital contributed by the partners) like a debt, not conventional, but debt. But the credit, the trust of the financial market, is based more on what you/they promise the managers that in a countable relationship of the passive one (and much less if it is deceiving). The things cannot be distorted to assist to the rights of those worthy of the society (that are sacred). These already know "with those who the rooms are played"; and, if they don't know it, it is their problem. It cannot load the inks on the current partners in favour of the futures, and even less in favour of the present managers. The cooperative society is an association of managers in democracy, each one of those which… he/she responds of its contribution, if the case arrives; but not before, "just in case". Because this is against the financial meaning, against the economical meaning and against the cooperative meaning.
Keywords: The partners' financial contributions; Social capital; Net Accountant; Patrimony; Private property; Limitation of responsibility; Economic profitability and financial profitability